Fine regulation of cI857-controlled gene expression in continuous culture of recombinant Escherichia coli by temperature. - Villaverde, A (1993)
The expression at different temperatures of the lacZ gene, which is controlled by the lambda pL and pR tandem promoters and the cI857 temperature-sensitive repressor, was studied in Escherichia coli continuous cultures. At temperatures between 30 and 42 degrees C, beta-galactosidase activity behaved according to an exponential equation. By inducing a culture at a temperature within this range, predefined, nearly constant submaximal levels of gene expression and recombinant product yield can be obtained.